Pengembangan Produk Asam Durian Berbasis Proyek Etnosains dalam Pendidikan Kimia: Menganalisis Kreativitas Calon Guru Kimia - Maria Erna; Siti Nazhifah; Sri Haryati; Putri Adita Wulandari; Muhammad Imam Rahmatullah (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to examine how an ethnoscience-based durian acid product-development project functions as a PCK-driven creative learning environment for prospective chemistry teachers and to analyze creativity across elaboration, originality, problem solving, and synthesis. A Classroom Action Research (CAR) design with an embedded mixed-methods approach was employed involving 68 fifth-semester pre-service chemistry teachers at the University of Riau. The intervention integrated Project-Based Learning (PjBL) stages—orientation, planning, implementation, and evaluation—within Plan–Act–Observe–Reflect cycles. Data were collected using creativity questionnaires, classroom observations, and interviews, and triangulated to validate findings. Results showed high agreement (74–93%) across creativity dimensions during orientation–implementation, supported by observed evidence of detailed planning, novel product ideas, and iterative troubleshooting. However, more neutral responses emerged during evaluation, indicating difficulties in evidence-based reflection and conceptual integration. The core chemistry concepts addressed included fermentation chemistry, pH interpretation, solution dilution, and acid strength comparisons. Triangulation was generally convergent, with partial divergence in originality during evaluation due to discrepancies between self-perceived novelty and observed pedagogical innovation. These findings suggest that ethnoscience-enriched PjBL effectively promotes creative PCK development, but requires structured scaffolding to strengthen data-driven justification and synthesis during reflective evaluation.